CONTRIBUTIONS OF REXLAB/UFSC TO THE PROMOTION OF MAKER CULTURE IN BASIC EDUCATION: A CASE STUDY ON THE TECHNOLOGY INTEGRATION IN EDUCATION PROGRAM (INTECEDU) - da Silva, Fabiana Regina; de Carvalho, Francisco Rogério; Dandolini, Gertrudes Aparecida; de Souza, João Artur; Thomé, Zeina Rebouças Correa (Seven Editora, 2025)
The maker culture, with its focus on practical and collaborative learning, has gained prominence in education. However, there are still challenges to its implementation in basic education. The Remote Experimentation Laboratory (REXLAB) at the Federal University of Santa Catarina (UFSC) stands out for its efforts in promoting maker culture in basic education through the Technology Integration in Education Program (INTECEDU). Aiming to analyze how REXLAB/UFSC promotes maker culture in basic education through the INTECEDU program, this study employed a qualitative approach. Data collection procedures included interviews with eight informants, including members of REXLAB/UFSC, as well as a visit to the Laboratory’s makerspace. The collected data were analyzed using Braun and Clarke’s Thematic Analysis, seeking to identify patterns of meaning within the dataset. The results indicate that REXLAB/UFSC has been essential in creating innovative resources and methodologies, promoting the integration of technology in education. The research highlights the role of REXLAB/UFSC in teacher training, the development of materials, and the creation of collaborative spaces for implementing maker culture in schools. The findings point to the need for effective public policies for the implementation of maker culture in Brazilian basic education.DOI: https://doi.org/10.56238/sevened2025.038-051